(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Body image is a multidimensional construct and refers to a Person’s Perception and attitudes, including feeling, thoughtsand behaviours regarding their own body and appearance. The link between weight status and body image is complex, that body imagemight be affected by overweight through psychological distress, which has an impact on quality of life. Body image is an essentialaspect of young girl’s self-definition and individual identity which is influenced by various biological, psychological and social factors.Excessive concern about body image, body image misconception are leading to dissatisfaction, disturbed eating patterns, affecting thenutritional status and also leading to depression and anxiety disorders. This research study therefore sought to assess the level of anxietyamong overweight and obese young girls with body image disturbance.Material and Methods: A quantitative descriptive study was conducted to assess the level of anxiety related to body image disturbanceamong study participants. A structured self-administered questionnaire was used to assess the baseline data. Total of 248 young girlswere screened for body mass index and among that 50 overweight and obese girls with body image disturbance (using body imagedisturbance scale) were selected using convenient sampling technique and also the anxiety level of the girls with body image disturbancewere measured using Hamilton anxiety scale. Informed consent was obtained from all the participants.Result: The study unveiled that among 248 young girls 12 were obese, 38 were overweight and 198 girls were in normal weight andunderweight. Hence it showed that every 1 in 5 young girls are overweight and obese. The study also revealed that 4(8%) of younggirls had mild body image disturbance, 27(54%) of them had moderate body image disturbance and 19(38%) of them had severe bodyimage disturbance. It also showed that 18(36%) had mild anxiety,15(30%) had moderate anxiety,17(34%) had severe anxiety. The meanscore of body image disturbance was 22.06+8.50 and the mean score of anxiety was 21.08 +12.22. The calculated Karl Pearson’scorrelation value of r=0.590 shows a moderate positive correlation which was found statistically significant at P < 0.001 level. It alsorevealed that only education of demographic variable (p=0.038) had shown significant association with level of anxiety.Conclusion: The study revealed that every 1 in 5 young girls had higher BMI more than 25kg/m2 and all the girls with higher BMI hadbody image disturbance and it also shows that all the girls with higher BMI had anxiety towards their body image. It also shows themoderate positive correlation between body image disturbance and the level of anxiety. This clearly infers that when body imagedisturbance increases then the anxiety level of the young girls also increases. This need to increase awareness and importance of healthydietary pattern and regular physical activity to improve the physical appearance, self-esteem, perception and satisfaction among younggirls.